Mechanisms for science to shape US living marine resource conservation policy. (15th December 2017) - Merrick, Richard; ,
Abstract: National Oceanic and Atmospheric Administration Fisheries are responsible for the stewardship of the US living marine resources and their habitat and for providing productive and sustainable fisheries, safe sources of seafood, the recovery and conservation of protected resources, and healthy ecosystems to the nation. Their approach to conservation requires, by legislative mandates, that management be informed by science. It has evolved into a four-step approach to providing this advice: (i) the national framework for conservation science, (ii) region specific implementation, (iii) development of unbiased, scientific advice as required by the framework, and (iv) scientists acting, as appropriate, as advocates and science communicators. This approach has been a conservation success where, e.g. 92% of known managed fish stocks are no longer being overfished and 84% of known stocks are at healthy levels, with the latter including 43 stocks rebuilt from depleted levels. In a changing marine climate, it is all the more important that marine conservation decisions be driven by science.